Perawatan Luka Diabetes Melitus Dengan Metode Modern Dressing - Syauqi Naufal Dzaki; Eko Julianto; Fida Dyah Puspasari (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Background : diabetes is a metabolic disorder characterized by hyperglrcrmia or high blood sugar levels due to the body’s inability to produce insulin or decreased sensitivity to insulin. Indonesa has the second highest diabetes mortality rate in the world. Two-thirds of diabetics in Indonesia are not aware of their condition, they may delay seeking treatment until it is too late to perform wound care. Modern wounds are better able to accelerate wound healing in patients with diabetes melitus. Purpose : describe the provision of wound care in diabetic patients melitus using the modern dressing. Method : data collection method using descriptive analysis with case study approach. Results : after being given the implementation of using modern dressing, the results areeffective for wound care in pateients with diabetes melitus wounds. This is evidenced by the change in wound size, 3cm x 3 cm belonging to a score of 2 p x l 4<16 to 3cm x 2cm. Coclusion : based on the results of a case study, modern nalut dressing is effective in accelerating the healing process of diabetes melitus wound.